The Hinge of Time: Mothers and Sons in Barthes and Augustine. (3rd July 2021) - Giusti, Francesco
ABSTRACT: Reading Augustine's Confessions after Roland Barthes's La Chambre claire ( Camera Lucida ) and Journal de deuil ( Mourning Diary ) helps to delineate an often-overlooked problem in the Confessions : the reality of the past outside of one's own personal memory. From a theological perspective, the past is grounded in God's eternity. Yet, when it comes to the narration of his own past, Augustine seems to need evidence of its reality. His mother Monica is the hinge that connects the unfolding of his story and the presentness of all time in God. One's own mother, not the figure of the Mother, appears to be the basis of confession and its temporality: she allows the past and the future to intersect the present of Augustine's telling of his story or Barthes's viewing of the photograph. Barthes's mother, in fact, reveals herself as the punctum that opens up what would otherwise be a moment of the past frozen in its image and makes that past operative in the present of the son-observer. To explore Barthes's affinities with Augustine, the article also looks at Jacques Derrida's "Circonfession" ("Circumfession") and Jean-François Lyotard's La Confession d'Augustin ( The Confession of Augustine ), which show revealing differences from both Augustine and Barthes and, along with Julia Kristeva's "Stabat Mater" and "Le vréel" ("The True-Real"), help to reassess the "mad" proposition of a mysticism of photographic technology offered in La Chambre claire .